Determinan Minat Mahasiswa Berinvestasi di Pasar Modal - Khoirudin, Rifki; Rasyiid, Septianto Al (Indonesian Journal Publisher, 2023)
This study aims to determine the effect of income, investment knowledge, investment benefits, capital market training, and motivation on students' interest in investing in the capital market, this study uses Multiple Linear Regression Analysis. The type of research used is a type of quantitative research. The population in this study is students in the Yogyakarta area. The sampling technique in this study used snowballs. The sample size was 110 respondents. Data was collected through questionnaires. The results of this study show that investment benefits and investment motivation have a positive and significant effect on students' interest in investing in the capital market. Meanwhile, income, investment knowledge, and capital market training do not affect students' interest in investing in the capital market.